THE COURSE OF PREGNANCY IN WOMEN WITH METABOLIC SYNDROME IN VIEW OF PATHOGENETIC ROLE OF THROMBOPHILIA - E. B. Perederyaeva; T. B. Pshenichnikova; E. V. Donina; A. D. Makatsariya; D. L. Kapanadze (IRBIS LLC, 2016)
Metabolic syndrome is widespread among women of reproductive age. Metabolic syndrome is associated with at higher risk of developing various obstetric complications. The endothelial dysfunction, proinflammatory status and thrombophilic status may play an important role in impaired invasion cytotrophoblast and impaired placental developmentin women with metabolic syndrome.